How fast do cardioactive steroids act independently of diffusion in guinea-pig myocardium? - Ebner, F. (1987)
1 The rate of onset of the inotropic effect of different cardioactive steroids (in order of increasing potency: dihydroouabain, digoxigenin, digoxin, ouabain, digitoxin) was studied in guinea-pig papillary muscles stimulated at 0.5 Hz. For an estimate of diffusion rate the time to defined levels of effect was evaluated in relation to the diameter of cylindrical muscles. 2 The dependence of onset rates on muscle diameter was more pronounced with a highly potent steroid, e.g., digitoxin, than with a less potent compound, e.g., dihydroouabain; that is, the apparent rate of diffusion was inversely correlated with the inotropic potency. Reduction of the ratio of receptor to steroid concentration with increase of ouabain or K+ concentration enhanced the apparent rate of diffusion. 3 Extrapolation to negligibly short diffusion distance indicated that the effects of the various steroids develop faster in the absence of diffusion. The effect of 50 mumol l-1 of dihydroouabain appeared more quickly than with ouabain in the perfused heart. The time courses of the inotropic effect in perfused hearts and in papillary muscles of diameters less than 0.75 mm were superimposable, indicating that the onset of the dihydroouabain effect was not controlled by diffusion. 4 After the interference of diffusion had been excluded, the rates of onset of action correlated inversely with the inotropic potencies of the steroids. The dissociation rate of the drug-receptor complex appeared to be related to the different receptor affinities.